Global efficiency and profitability: Cooperatives as social innovation agents vs. Joint stock companies in the agri-food sector - Elena Meliá-Martí; Adoración Mozas-Moral; Enrique Bernal-Jurado; Domingo Fernández-Uclés (Journal of Innovation & Knowledge (JIK), 2024)
Cooperativism, as an agent of social innovation, significantly contributes to fostering a dynamic economy and plays a fundamental role in rural areas. Analyses of profitability in cooperatives versus Investor-Owned Firms (IOFs) show disparate results depending on the methodology and indicators used. This disparity of results is largely due to the fact that common indicators are used in the business sphere that do not take into account the duality of investor-supplier members in cooperatives. This paper deals with a comparative analysis of the efficiency and profitability of cooperatives and IOFs, which takes into account the cooperative specificity as far as partner-producer duality is concerned. The populations analyzed are the olive oil producing companies in Andalusia and the methodology used is twofold: DEA, in the case of efficiency, and probit regression for the analysis of profitability. For the latter, a cooperative global profitability indicator has been defined. The results point to a superiority of the cooperatives in terms of both efficiency and overall profitability compared to the IOFs, which denotes a greater capacity to better remunerate the producer, especially in smaller companies. However, this superiority disappears as the cooperative gains dimension. Our findings show that the relative performance of cooperatives and IOFs varies by size. This reality warrants the attention of both society and governments, prompting the need for the development and implementation of public policies aimed at their growth and safeguarding. Additionally, it initiates a pathway for further research into other sectors of activity.
Keywords: Q14; D24; L25; 650; Cooperative; Economic profitability; DEA; Social innovation; Olive sector; IOFS